Artificial Induction and Genetic Structure Analysis of Tetraploid Turbot Scophthalmus maximus - Wu, Zhihao; Wang, Lijuan; Lu, Yunliang; Zhu, Xiangping; Yue, Xinlu; You, Feng (Frontiers in Marine Science, 2019)
Artificial tetraploid induction is one of the important techniques of fish chromosome manipulation, and it is the first step for triploid breeding. There are a few reports to artificial induction of tetraploid in marine fish. The induction and survival rate was usually low. We firstly optimized the tetraploid induction conditions in turbot Scophthalmus maximus, one of the most important maricultural fish in China and Europe. For the initiate time of treatment, which is the most important factor in tetraploid induction, the first cleavage index was used to reduce the influences of genetic origin and environment factors. Overall, the optimal initiation time for pressure shock was 15 min before the first cleavage at 14.8-15.5℃. The optimal treatment pressure and treatment duration were 67.5 MPa and 6 min. The regression equation prediction model was: The optimal initiation time = 0.982 FCI - 12.182 or the optimal initiation time = 0.85 FCI. Then two tetraploid induction (4n1 and 4n2) populations were obtained under the optimal conditions with diploid controls (2n1 and 2n2). The induction rate in tetraploid induction (4n) population could reach 100%. The genetic structure of artificial induced tetraploid turbot was also studied. Two to four alleles were detected in diploid (2n) and 4n populations, respectively. Private alleles were only appeared at locus sma-usc21, with two alleles lost in 4n populations. Eleven and fourteen loci in 2n and 4n population showed a negative genetic deviation index. 3D-FCA analysis showed that the two diploid 2n and two 4n populations have obvious differences. The numbers of locus deviating from Hardy-Weinberg equilibrium in 2n1, 4n1, 2n2, 4n2 populations were 6, 9, 12, 7, respectively. Overall, 12 loci in either 2n or 4n population deviant from Hardy-Weinberg equilibrium. Tetraploid induction population showed lower heterozygosity and higher heterozygote deletion.